2023
DOI: 10.3389/fimmu.2023.1086930
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 improves allograft osteointegration and directly enhances osteoblasts differentiation

Abstract: IntroductionAllografts are the most common bone grafts for repairing osseous defects. However, their use is associated with an increased risk for infections, donor disease transmission and osteointegration deficiency. Resolvin D1 (RvD1) is an endogenous lipid with a scientifically proven pivotal role in inflammation resolution and osteoclastogenesis inhibition. Yet, its biological relevance as a potential bone regenerative drug has been scarcely studied. Here, we aim to investigate the RvD1 effect on allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…As both IL‐17 and ferroptosis are closely related to bone repair and destruction (Dar et al, 2023; Pinto et al, 2023; Wang et al, 2023), we used erastin to aggravate ferroptosis and investigate the role of IL‐17 + erastin in experimental periodontitis mice. IHC staining was carried out to investigate the expression of IL‐17RA and its cellular localization in periodontal tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As both IL‐17 and ferroptosis are closely related to bone repair and destruction (Dar et al, 2023; Pinto et al, 2023; Wang et al, 2023), we used erastin to aggravate ferroptosis and investigate the role of IL‐17 + erastin in experimental periodontitis mice. IHC staining was carried out to investigate the expression of IL‐17RA and its cellular localization in periodontal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Our results also indicated that the levels of ferroptotic molecules, NRF2, GPX4 and SLC7A11, were lower in the experimental tissues than in the normal periodontal tissues (Figure1f-h). The results suggested that osteoblast ferroptosis may be associated with periodontitis.3.2 | Influence of IL-17 on erastin-induced alveolar bone resorption in the experimental periodontitis modelAs both IL-17 and ferroptosis are closely related to bone repair and destruction(Dar et al, 2023;Pinto et al, 2023;Wang et al, 2023), we used erastin to aggravate ferroptosis and investigate the role of IL-17 + erastin in experimental periodontitis mice. IHC staining was carried out to investigate the expression of IL-17RA and its cellular localization in periodontal tissues.…”
mentioning
confidence: 99%
“…In rat calvarial defects, a recent work by Jiang et al 3 showed that RvD1 had enhanced bone regeneration and vascularization potential. Similarly, Pinto et al 9 have shown that RvD1 may be a viable therapeutic bioagent for osseous regeneration following the placement of allografts. In contrast, limited information is available on the bone regenerative potential of RvE1, and no prior studies have reported the effect of local application of RvE1 alone or with bone graft in enhancing bone regeneration.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, Jiang et al3 demonstrated that a D variant of resolvins (RvD1) incorporated into nanopore scaffold and Pluronic F127 hydrogel group had enhanced bone formation and vascularization in rat calvarial defects compared to combined collagen 3D nanopore scaffold and pluronic F127 hydrogel group. Similarly, Pinto et al9 who also evaluated RvD1, demonstrated that RvD1 enhanced bone regeneration by increasing osteoblast differentiation and decreasing osteoclastogenesis and the RANKL/OPG ratio. The authors also showed that compared to a single administration of RvD1, repeated administration of RvD1 increased bone content by 135.92%.The outcome of this study showed the areas of NFB in all the study group.…”
mentioning
confidence: 88%
See 1 more Smart Citation